(untitled) (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
Kenyan beaches are multilingual spaces of encounters between European ‘package tourists’ and African beach vendors, but also play host to the social inequalities and marginalization of the ubiquitous sex tourism business. In contrast to well-researched youth language practices, often understood as playful linguistic trends, young beach boys’ patterns of foreign language acquisition and their multilingual performance at the beaches are based on economic survival and offer a different perspective on multilingual practice: Most of the male sex workers with broad linguistic repertoires undergo a painful process to learn the tourists’ languages, based on experiences of degradation, hostility and shame. The fluid translanguaging practices of marginalized speakers draw from Kiswahili and local Mijikenda languages while also incorporating a vast lexicon from tourist languages. At the same time, they serve a subversive function, evident in the modification of vulgar German lexemes, which allows marginalized sex workers to mimetically “speak back” to their female customers. In my overview paper, I aim to discuss the role of tourists’ languages in emerging translanguaging processes and I intend to investigate the “darker side” of heteroglossic repertoires in the tourism sector; where I claim that multilingual experience is often linked to and reflects marginality, exploitation, and social inequality.